Association of Oxidative Stress and Hyperglycemia Among Fertile and Infertile Females. - Ekta Arpita Andriyas; Sapna Smith Lal (International Journal of Pharma and Bio Sciences, 2024)
The life style, food habits now days promote abnormally high levels of free radicals and the decline of antioxidant defense mechanisms which at the end can lead to damage of cellular organelles and enzymes, increased lipid peroxidation, development of insulin resistance. Oxidative stress can later develop complications of diabetes mellitus. Studies suggest that Free radicals are formed disproportionately in diabetes by glucose oxidation, non-enzymatic glycation of proteins, and the subsequent oxidative degradation of glycated proteins. Persistent hyperglycemia also causes an increase in ROS. About 500 married females were included, of which 250 were fertile and 250 infertile married females of reproductive age 25-35 years with no history of metabolic disorder. The level of Random blood sugar, glycosylated hemoglobin, oxidative stress marker Melondialdehyde (MDA), and three antioxidant enzyme catalase (CAT), ceruloplasmin, and superoxide dimutase (SOD) were measured in both groups. The results of random blood sugar level and glycosylated hemoglobin showed significance between the two groups (P>0.0001), where the group II level was higher than group I. A significant (p>0.0001) increase in the MDA level and a significant (p>0.0001) decrease in the catalase, ceruloplasmin, and SOD in the infertile group when compared to the fertile group. The correlative study between the superoxide and Melondialdehyde indicated (r=-0.53, p<0.05) a significant negative correlation, similarly a significant negative correlation was found among Melondialdehyde and catalase (r = -0.29, p<0.05) as well as in between Melondialdehyde and ceruloplasmin (r=0.20, p<0.05). These results suggest that oxidative stress is related to the pathophysiology of fertility in females. Changes in blood sugar, glycosylated hemoglobin, and oxidative stress biomarkers, including superoxide dismutase, Catalase, and Ceruloplasmin, and their consequences are discussed in this research paper.